Ligtas Agtas a sustainable and disaster-ready resettlement area for the Agta community in Sitio Pulang Lupa - Ang, Shanelle Faith R.; Honorio T. Palarca (Quezon City College of Architecture, University of the Philippines Diliman, 2020)
Homes should feel safe and secure. This is not the case for Mount Kalbo’s Agta Community as they face the challenges of dealing with the risks of mass wasting devastating their homes and compromising the lives of their families every single day.
It is with high hopes that they will be given the opportunity to be resettled to Sitio Pulang Lupa and be provided with government support to rebuild a community that shall improve their living conditions and unify them together. This study merges the necessities of the Agta Community, which are resettlement, disaster preparedness, and improved living conditions into one landscape development in Sitio Pulang Lupa that addresses all issues raised by the Agtas and with consideration to the resettlement site involved. This landscape development comprises of spaces and facilities that reflect the culture and needs of the community. Aside from cultural representation and provision of spaces and facilities, disaster management protocols were also highlighted in the development by providing refuge landscapes to equip the Agtas with knowledge in case disaster occurs. To achieve the aforementioned vision for the Agtas, soil conditions are addressed to apply appropriate slope protection measures and enhance the environmental quality of the Agtas’ resettlement area. This shall address mass wasting threats that through this, Agtas shall finally feel secure and safe in their own homes. In the end, the Agta Community shall enjoy improved living conditions, cultural representation, and disaster preparedness towards sustainability.
Thesis (Bachelor of Landscape Architecture) -- University of the Philippines Diliman
Keywords: Cultural Representation; Disaster Preparedness -- Sitio Pulang Lupa; Mass Wasting -- Sitio Pulang Lupa; Refuge Landscapes -- Sitio Pulang Lupa; Resettlement -- Sitio Pulang Lupa